Production of Cultural and Symbolical Capital: Disney's Phenomenon - Mažeikis, Gintautas (Problemos, 2003)
The classical conception of capital constructed by Marx and notions of cultural and symbolical capital suggested by P. Bourdieu’s are compared in the article. Disney’s products are connected with institutionalisation and manipulation of the three forms of capital. Author of the article discusses relations and conflicts between cultural capital and the making of fetish and personification. Disney's politics of institutionalisation eliminates these conflicts and solves the problem of alienation among people within the corporation. Disney’s practices of auteur and animation prevents antagonism between property of the corporation and ambitions of creators. Historical analyses show how ideologies, conceptual paradigms, action models developed by Disney met wishes of the masses, implemented modern multiculturalism, diversification and supported social fragmentation. The article criticises Th. Adorno’s and W. Benjamin’s views where Disney’s corporation is considered as an expression of hegemonic industrial imperialism and a propagandist of American ideology. However, Disney is rather a producer of social discourses and new models of education. If even any corporation is ideological one, however stories and characters produced by Disney corporation (for example, ones about Winnie-the-Pooh, Aladdin, Alice, Mickey Mouse, Pinocchio, Pocahontas, Hercules) are mythological and philosophical parables which overpass ideological borders and open the door to the live and huge world. Humanistic and individualistic activities of Disney Corporation’s creation, co-operation with consumers, and development of education programs are emphasized in the article. Disney relies on investigation of basic cultural habitus, archetypes and symbols of thinking. In this way, Disney creates the world of fantasy, dreams and Utopias. The corporation uses pragmatism as a philosophical foundation. The only truth for the corporation is production of pleasure and profit for all consumers. Everybody could find a pleasure, psychological satisfaction and stimuli for socialization and cooperation in these miraculous lands. It gives Disney profit and growth opportunities.
Keywords: Marxist notion of capital; fetishism; personification; animation; institutionalisation; utopia